Evaluasi User Experience dengan Mengadaptasi meCUE Questionnaire pada Aplikasi KAI Access dan Aplikasi Tiket.com - Dea Annisa Larasati; Hanifah Muslimah Az-Zahra; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT. Kereta Api Indonesia (Persero) as one of the rail transportation service providers has KAI Access application for rail ticket bookings. One of the other train ticket purchase providers is the Tiket.com application. Users of these two applications still often encounter problems while using the app. One important aspect to be considered in developing a mobile application is user experience. This study aimed to find out the results of user experience evaluation found in both applications based on user experience using the meCUE questionnaire. meCUE questionnaire has 4 modules, Module I (product perceptions), Module II (user emotions), Module III (consequences of use) and Module IV (overall evaluation) and has a total of 34 statement items. This study first translated the meCUE questionnaire and then tested its validity and reliability. After obtaining valid and reliable questionnaire results, this questionnaire was distributed to 45 respondents who have used KAI Access application and Tiket.com application. Furthermore, the results of this questionnaire distribution will be processed into calculations on the meCUE questionnaire so that the UX evaluation results are obtained. The results obtained are KAI Access applications have the highest results on the usability indicator (5.75) and the lowest average value in the negative emotions indicator. The Ticket.com application has the highest yield on the usability indicator (5.25) and the lowest average score on the negative emotions indicator. The overall result of the average assessment for the Access KAI application is 3.8 and for the Tiket.com application is 3.3.